(untitled) (Research, Society and Development, 2024)
Understanding the terms urgency and emergency is essential for effective clinical decisions. Urgency refers to situations that require quick but not immediate attention, whereas emergency implies an imminent threat to life that requires immediate intervention. This study reviews the literature on the role of the pharmacist in the Mobile Emergency Care Service (SAMU) and other mobile health services, highlighting how these professionals contribute to the safety and effectiveness of patient care in critical situations. In this context, the presence of a pharmacist is fundamentally important in the support structure for patients, particularly in the analysis of medical prescriptions to ensure patient safety and treatment effectiveness. Recognizing the relevance of the pharmacist in healthcare, the research covers considerations about the Mobile Emergency Care Service (SAMU); Pharmaceutical Care through best practices in health services; the Collegiate Board Resolution (RDC No. 44 of August 17, 2009); and the provision of pharmaceutical services in urgent and emergency dynamics. This research was conducted using information from a bibliographic review, encompassing books, scientific articles, and journals. As results and discussions, the research considered 10 articles published between 2016-2023, which were relevant in discussing the proposed objective regarding the role of the pharmacist in the context of SAMU and other mobile health services. It was concluded that studies on the role of pharmacists are still shallow in the Brazilian literature. However, it was observed that when this professional is available in health service care, the population is better supported, highlighting a good quality of life.